Prevalence and risk factors for musculoskeletal problems associated with microlaryngeal surgery: A national survey. (10th June 2014) - Wong, Adrienne; Baker, Nancy; Smith, Libby; Rosen, Clark A.
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis Microlaryngeal surgery (MLS) presents ergonomic challenges to surgeons and potential risks for developing musculoskeletal symptoms (MSSx). This study describes prevalence and risk factors of MLS‐associated MSSx. Study Design Cross‐sectional survey. Methods A questionnaire was administered to members of the American Academy of Otolaryngology–Head and Neck Surgery. Outcome measures related to surgeon demographics, training, MLS experience, operating room setup, experience of MSSx in relation to MLS, treatment sought, and practice changes due to MSSx. Results Response rate was 9.2% (n = 476); 83% reported musculoskeletal symptoms during MLS, and 21% reported rest breaks during MLS. Taking breaks was independently associated with back support lack (odds ratio [OR] = 2.08) and surgery lasting >30 minutes (OR = 1.68). Areas most commonly affected were neck, upper back, shoulder, and lower back. Ten percent reported treatment for MLS‐related MSSx. Some respondents reported major practice changes due to MSSx, including fewer cases, ceasing to perform MLS, applying for disability, and early retirement. Conclusions Musculoskeletal symptoms are common (83%) among surgeons performing microlaryngeal surgery. Findings suggest multiple factors may contribute to development of MSSx in otolaryngologists. Risk factors for MSSx and taking breaks during surgery include average case operating time >30 minutes and absence of back support. Previous studies have identified neck flexion and lack of arm support as associated with risk of musculoskeletal injury. This study demonstrates that MSSx related to surgery do occur in otolaryngologists, and that poor surgical ergonomics may play a role. Surgeons should consider proper support and positioning during MLS to protect their health. Level of Evidence NA Laryngoscope, 124:1854–1861, 2014